Faster Intercalation Pseudocapacitance Enabled by Adjustable Amorphous Titania Where Tunable Isomorphic Architectures Reveal Accelerated Lithium Diffusivity. Issue 7 (21st April 2022) - van den Bergh, Wessel; Larison, Taylor; Jesus Jara Fornerod, Maximiliano; Guldin, Stefan; Stefik, Morgan
Abstract: Intercalation pseudocapacitance is a faradaic electrochemical phenomenon with high power and energy densities, combining the attractive features of capacitors and batteries, respectively. Intercalation pseudocapacitive responses exhibit surface‐limited kinetics by definition, without restriction from the collective of diffusion‐based processes. The surface‐limited threshold (SLT) corresponds to the maximum voltage sweep rate ( v SLT ) exhibiting a predominantly surface‐limited current response prior to the onset of diffusion‐limitations. Prior studies showed increased lithium diffusivity for amorphous titania compared to anatase. Going beyond prior binary comparisons, here a continuum of amorphous titania configurations were prepared using a series of calcination temperatures to tailor both amorphous character and content. The corresponding amorphous‐phase v SLT increased monotonically by 317 % with lowered calcination temperatures. Subsequent isomorphic comparisons varying a single transport parameter at a time identified solid‐state lithium diffusion as the dominant diffusive constraint. Thus, performance improvements were linked to increasing the lithium diffusivity of the amorphous phase with decreased calcination temperature. This remarkably enabled 95 % capacity retention (483±17 C/g) with 30 s of delithiation (120 C equivalent). These results highlight how isomorphic sample series can reveal previously unidentified trends by reducing ambiguity and reiterate the potential of amorphization to realize increased performance in known materials. Abstract : Tunable amorphization : The intercalation pseudocapacitive kinetics of amorphous titania were found to vary significantly with granular adjustments to calcination conditions. Using a series of single‐variable adjustments to transport processes, the performance changes were attributed largely to modification of solid‐state lithium diffusivity. This study emphasizes the differences amongst the continuum of amorphous configurations and reveals new opportunities for improved devices.